Perilaku Pencegahan Penularan Covid-19 Remaja Di Sidoarjo - Irni Setyawati; Kusniyati Utami; Dian Soekmawaty Riezqy Ariendha (2020)
Pandemic Coronavirus Disease 2019 (Covid-19) is still being felt in various countries in the world, including Indonesia. There were 43,450 positive cases of Covid-19 in East Java until September 29, 2020 (East Java Province Covid-19 Task Force, 2020). Sidoarjo Regency has positive cases of Covid-19 until September 30, 2020, totaling 6,236 cases (Communication and Informatics Office of Sidoarjo district, 2020). Wijayanto (2020) reports that many young people aged 15-25 years are exposed to Covid-19 because of the habit of hanging out in cafes or coffee shops by not keeping physical distancing and removing their masks. The purpose of this study was to analyze the prevention behavior of teenagers from Covid-19 in Sidoarjo. The research design was analytic observational with cross sectional approach. The population of respondents is male or female aged 16-19 years who live in Sidoarjo. Samples were obtained through voluntary sampling technique. Data collection used a google form which was distributed via WhatsApp in August 2020 to 18 sub-districts. The questionnaire received responses from 176 people from 13 districts. Bivariate analysis using the Chi Square test. The results showed that there were significant differences in the prevention behavior of Covid-19 transmission based on gender (p value = 0.02) and there were significant differences in the prevention behavior of Covid-19 transmission based on knowledge (p value = 0.0001). Suggestions for the Sidoarjo regency government are to increase education on the prevention of Covid-19 transmission with various methods and media that are preferred by teenage boys and in crowd centers.